النتائج قريبة ومتوسطة الأمد لطي المعدة بالتنظير لعلاج البدانة المرضية - سعد أحمد (Latakia University Journal -Medical Sciences Series, 2018)
Gastric plication is a new restrictive method of bariatric surgery, distinguished by its ease, safety, good results and low cost. This research was performed on 30 patients who were operated in the lattakia hospitals, we followed the patients and their results for 18 months after the surgery. the analysis of the results showed an excellent efficiency in terms of excess weight loss (EWL) after 18 months (63%) and a low rate of complications (3.33%) and failure (6.66%(. Comparison with other studies showed similar results to the level of weight loss and complications. In conclusion we can say that gastric plication is an effective and safe method for the treatment of morbid obesity provided that patients are well chosen and well followed postoperatively. عملية طي المعدة بالتنظير هي إحدى الطرق الحاصرة الحديثة لجراحة البدانة المرضية بالتنظير، تتميز بسهولة الإجراء وقلة الاختلاطات والتكلفة المنخفضة والنتائج الجيدة. أجريت الدراسة على ثلاثين مريضاً أجريت لهم هذه الجراحة في مشافي اللاذقية وتمت متابعتهم ومراقبة النتائج لمدة 18 شهر بعد الجراحة، تحليل النتائج أظهر فعالية ممتازة من ناحية معدل فقد الوزن الزائد (EWL) بعد سنة ونصف من الجراحة بلغ بالمتوسط 63% مع معدل منخفض لحدوث الاختلاطات (3.33%) وفشل في فقدان الوزن بنسبة 6.66%. المقارنة مع دراسات أخرى أظهرت نتائج متقاربة من حيث الفعالية و الاختلاطات. بنتيجة الدراسة توصلنا أن طي المعدة بالتنظير طريقة آمنة وفعالة وقليلة الاختلاطات لعلاج البدانة المرضية بشرط الاختيار الجيد للمرضى وحسن المتابعة بعد العمل الجراحي.